2020
DOI: 10.1017/s0959774320000037
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Houses and Communities at Çatalhöyük: A Building Biography Approach to Prehistoric Social Structure

Abstract: Houses are rich resources for understanding prehistoric social structure. However, conventional working methods often handle houses as stable entities that reflect the nature of households and other social units. Social groups may be inadvertently rendered static in the process. A biographical understanding, in which the on-going transformation of built space is part of different kinds of human collaboration, allows us to explore the dynamic qualities of past communities. I examine detailed life-histories of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
0
11
0
1
Order By: Relevance
“…This is demonstrated by shifts in house architecture, from more closed units to more open dwellings in which daily activities took place in the open, uniting groups of houses into wards. Archaeological household data from Çatalhöyük show similar patterns of supra-household integration (Kay 2020). At Çatalhöyük, some houses did not have ovens, hearths, or storage but were still being used; Kay suggests that people may have eaten their meals with other nearby households that did have these features, thereby reinforcing membership as part of a broader community outside the household.…”
Section: Introductionmentioning
confidence: 88%
“…This is demonstrated by shifts in house architecture, from more closed units to more open dwellings in which daily activities took place in the open, uniting groups of houses into wards. Archaeological household data from Çatalhöyük show similar patterns of supra-household integration (Kay 2020). At Çatalhöyük, some houses did not have ovens, hearths, or storage but were still being used; Kay suggests that people may have eaten their meals with other nearby households that did have these features, thereby reinforcing membership as part of a broader community outside the household.…”
Section: Introductionmentioning
confidence: 88%
“…Pearson et al (2021) found statistically significant differences between those buried in buildings based on C and N isotopes. The notion that groups of houses prepared food and ate together is supported by detailed work on house histories (Kay 2020;2022). In several buildings there is an absence of hearths or ovens in particular phases, suggesting that more than one building was involved in food preparation at certain times.…”
Section: The Social Process In the Early And Middle Levelsmentioning
confidence: 99%
“…First, it ignores the detailed evidence of continual change and realignment in the organisation of daily activities. Kevin Kay (2020) has conducted detailed stratigraphic studies of the sequences of activities in houses. There is continual change in the location and number of hearths and ovens, platforms, burials and storage bins.…”
Section: Fig 3 Schematic Diagram Of Nested Scales Of Social Grouping ...mentioning
confidence: 99%